Dipterocarpus genus / Azmarihan Hassim - Hassim, Azmarihan (2009)
Dipterocarpus is an important Indo-Malayan genus which is distributed from south India and Sri Lanka throughout western Malaysia to the Philippines. It includes about 69 known species. Thirty-one species are known to occur in the Malay peninsula. Only about half on the peninsular species are common and well known to foresters. Dipterocarpus is a clearly defined genus in the botanical sense, and its systematics is less confused than that of most groups of the family.